Analisa Prestasi Mesin “MAK 8M453 C” Pada PT. PLN (Persero) Sektor Pembangkitan Kendari Unit Pembangkit Wua-Wua - Zailand, La ode Muhammad; Salimin, Salimin; Kadir, Abd. (Teknik Mesin Universitas Halu Oleo, 2020)
One type of prime movers that is widely used is a heat engine, a machine that uses thermal energy to do mechanical work. This study aims to determine how much achievement is produced by the MAK 8M453C Diesel engine. In this study the authors used a thermometer, compression tester and multimeter to measure and calculate the data taken in the study. Calculation results obtained Ni indicated power generated is 3489.9 hp, Ne Effective Power of 31025 hp, while the engine power according to engine data is 3804.3 hp or 2800 Kw. From these figures, power decreased slightly by 8.2 %. This is caused by pressure loss of spraying and wear and tear on some parts of the engine. Effective fuel consumption of 0.12 kg/hp-hr and effective thermal efficiency of 52.26 %. Keywords: Power of indication, effective power, efficiency.